Reaction Kinetic Model for 2,4-Dichlorophenoxyacetic Acid Decomposition in Aqueous Media Including Direct Photolysis, Direct Ozonation, Ultraviolet C, and pH Enhancement - Gilliard, María Belén (2013)
This report presents a comprehensive study of the degradation kinetics of herbicide 2,4-dichlorophenoxyacetic acid (2,4-D) using ozone with and without intensification with ultraviolet C (UVC) radiation. The byproducts cause several series-parallel reactions that compete with the process of photon absorption when radiation is applied. Five processes were analyzed separately: (i) the direct photolysis of 2,4-D and its main byproducts, (ii) direct ozonation in the absence of hydroxyl radicals using tert-butyl alcohol as radical scavenger, (iii) the oxidation when ozone reacts in parallel with hydroxyl radicals, (iv) the reaction enhanced with UVC radiation, and (v) the oxidation improved by pH modifications. A kinetic model was developed on the basis of the main reaction byproducts. The corresponding parameters of the reacting system were determined (nine of its 29 kinetic constants were previously unknown). Simulation results, including a rigorous description of the reacting system and the radiation field (having dark and illuminated volumes), agree very well with the experimental data.